Mapping of Goosegrass (Eleusine indica) Herbicide Resistant-Glyphosate Populations and Their Distribution on Rubber Fields at Rambutan Estate PTPN III - Agustinus Kristian Purba; Edison Purba; Charloq charloq (Universitas Sumatera Utara, 2018)
ABSTRACT Goosegrass (Eleusine indica) on rubber fields at Rambutan estate PTPN III had been sprayed using glyphosate for 28 years continuously. Lately it was reported that the herbicide glyphosate was no longer effective to control E.indica in that area. The objective of this study was to determine the spread and resistance levels of E. indica populations to glyphosate found in 14 Divisions of Rambutan Estates. The 14 populations were compared to a population collected from the University of Sumatera Utara where no herbicides had been sprayed previously. The plants were sprayed with 480 g a.i IPA glyphosate at 4-5 leaf stage. Experiment was arranged using fully randomized design non factorial, with the populations of, ESU0, ESU5.1, ESU5.2, ESU5.3, ESU5.4, ESU5.5, ESU5.6, ESU5.7, ESU5.8, ESU5.9, ESU5.10, ESU5.11, ESU5.12, ESU5.13, and ESU5.14, of which each population was made in 4 replications.Results showed that of 14 populations of goosegrass, 8 populations were “very resistant” and 6 populations were “resistant” to glyphosate. Thus the entire populations have developed to become resistant to glyphosate. Keywords : Distribution, eleusine indica, glyphosate, resistance, rubber estate